Implementasi Metode Rapid Application Development Pada Sistem Informasi Laboratorium Berbasis Web (Kasus: Laboratorium Mikrobiologi dan Genetika Universitas Nasional) - Prasetyo, Ricky Budhi; Nurhayati; Farahdinna, Frenda (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The Microbiology and Genetics Laboratory at the Faculty of Biology and Agriculture, National University, has a Laboratory Assistant who is technically responsible for managing various aspects of the laboratory. Laboratory management includes the administration of borrowing space, tools, books, as well as setting up the laboratory as a place for research and practicums. Administrative processes that are still manual cause delays in borrowing space, tools and books in the laboratory. To overcome this problem, this research aims to build a management information system (SIMLAB) that can help make laboratory assistants’ tasks easier. System validation is carried out using the black box method. Chatbot system testing involves sentence similarity tests and word similarity test results. The test results show that if the similarity of sentences or words is more than 70%, the chatbot can identify questions and provide answers based on the dataset. However, if it is less than 70%, the chatbot will give the default answer "I don’t understand the meaning of your question"